6.5 Ghz And 10.2 Ghz Path Loss Measurements And Modeling For 5G Communications System Prediction - Nor Raihan Zulkefly; Tharek Abdul Rahman; Marwan Hadri Azmi; Omar Abd. Aziz (CleverMind Solution Pvt Ltd, 2024)
Non-Indexed Publication